AN ANALYSIS OF CHARACTERS IN ‘’I LOVE YOU MOM’’ SHORT STORY BOOK BY ARLEEN AMIDJAJA - -, Zahroni (JURNAL LITERARY CRITICISM, 2016)
Character is a system of beliefs and practices that direct the actions of an individual. By analyzing the characters, we can understand the human characters in everyday life. Therefore, researchers are interested in analyzing the characters in '' I Love You Mom'' Short Story Book. The problem of this study are: (1) What arethe characters in ?I Love You Mom??short story book? (2) What are the moral values that can be found in ? I Love You Mom?? Short Story Book? The researchertook five short stories to analyze. This study useda descriptive qualitative method to analyze and interpret the research object sentence in ??I Love You Mom.??book. The stepto obtain the data was collectingsources of the data from five short stories in ??I Love You Mom.??book. After that, the researcherselected data and made conclusion. The results of this research are: (1) related about the character, (2) related about moral value. The researcher expects this research will be useful for other researchers who are eager to know more about characters. Key words: Character, morals, values, short story.